The Education Concept of Digital Literacy in Indonesian Young Civil Society (Analysis of Hashtag Community on Twitter) - Sa’diyah, Maemunah; Rofi’ah; Mas’udin; Ihsan Pratama, Arizqi; Putri Amalia Shaleha, Gita; Syawaludin Pangestu, Ridho (TOPAZART, 2023)
Social interaction in virtual media create many communities, and have different functions and goals. In the s elf existence young generation context, this qualitative research results there are three community models formed in Twitter. First, self exsistence build in critical social issue, second, the community that participates in criticizin social issue and creating the existence of popular netizens, lastly, the community that builds existence only as a popular netizen. In the three community models, the second community model can be education concept of digital literacy, because they communication strategy developed has an impact on the broad, deep and critical references in order to be able to have good discussions.